PENGARUH PERBANDINGAN SOSIAL TERHADAP SCHADENFREUDE PADA INDIVIDU DEWASA AWAL YANG DIMEDIASI OLEH HARGA DIRI - Larasati, Sarah Rahima; Chotidjah, Sitti; Wulandari, Anastasia (Jurnal Psikologi, 2024)
The study aimed to test the effect of social comparison on schadenfreude in early adulthood individuals mediated by self-esteem. Respondents were individuals aged 18 to 24 (n = 350) who were taken using accidental sampling techniques. The Iowa-Netherlands Social Comparison Measurement (INCOM) with a reliability of 0.720 was used to measure an individual’s social comparison level. Schadenfreude scale with a reliability of 0.925 was used to see the individual’s schadenfreude, and the Rosenberg Self-Esteem Scale (RSES) with a reliability of 0.872 was used to measure the individual’s self-esteem level. Data were analyzed by using simple and multiple regression analysis techniques with a significance level of 0.05. The results of this study showed that self-esteem mediates the effect of social comparison on schadenfreude in early adulthood individuals by providing them with a suppressor effect.